Antidiabetic potential of Lysiphyllum strychnifolium (Craib) A. Schmitz compounds in human intestinal epithelial Caco-2 cells and molecular docking-based approaches - Kunwadee Noonong; Kanta Pranweerapaiboon; Kulathida Chaithirayanon; Kantamat Surayarn; Phicharinee Ditracha; Narin Changklungmoa; Pornanan Kueakhai; Poonsit Hiransai; Kingkan Bunluepuech (BMC, 2022)
Abstract Background Lysiphyllum strychnifolium (Craib) A. Schmitz, a traditional Thai medicinal plant, is mainly composed of polyphenols and flavonoids and exhibits several pharmacological activities, including antioxidant, anticancer, antimicrobial, and antidiabetic activities. However, the mechanism by which pure compounds from L. strychnifolium inhibit glucose catalysis in the small intestine and their effect on the glucose transporter remain unknown. Methods The objectives of this research were to examine the effect of 3,5,7-trihydroxychromone-3-O-𝛼-L-rhamnopyranoside (compound 1) and 3,5,7,3',5'-pentahydroxy-flavanonol-3-O-𝛼-L-rhamnopyranoside (compound 2) on the inhibition of α-amylase and α-glucosidase, as well as glucose transporters, such as sodium-glucose cotransporter 1 (SGLT1), glucose transporter 2 (GLUT2), and glucose transporter 5 (GLUT5), using Caco-2 cells as a model of human intestinal epithelial cells. Additionally, the binding affinity and interaction patterns of compounds against two receptor proteins (SGLT1 and GLUT2) were determined for the first time utilizing a molecular docking approach. Results In the α-amylase inhibition assay, a concentration-dependent inhibitory response was observed against the enzyme. The results indicated that compound 1 inhibited α-amylase activity in a manner similar to that of acarbose (which exhibit IC50 values of 3.32 ± 0.30 µg/mL and 2.86 ± 0.10 µg/mL, respectively) in addition to a moderate inhibitory effect for compound 2 (IC50 = 10.15 ± 0.53 µg/mL). Interestingly, compounds 1 and 2 significantly inhibited α-glucosidase and exhibited better inhibition than that of acarbose, with IC50 values of 5.35 ± 1.66 µg/mL, 510.15 ± 1.46 µg/mL, and 736.93 ± 7.02 µg/mL, respectively. Additionally, α-glucosidase activity in the supernatant of the Caco-2 cell monolayer was observed. In comparison to acarbose, compounds 1 and 2 inhibited α-glucosidase activity more effectively in Caco-2 cells without cytotoxicity at a concentration of 62.5 µg/mL. Furthermore, the glucose uptake pathways mediated by SGLT1, GLUT2, and GLUT5- were downregulated in Caco-2 cells treated with compounds 1 and 2. Additionally, molecular modeling studies revealed that compounds 1 and 2 presented high binding activity with SGLT1 and GLUT2. Conclusion In summary, our present study was the first to perform molecular docking with compounds present in L. strychnifolium extracts. Our findings indicated that compounds 1 and 2 reduced glucose uptake in Caco-2 cells by decreasing the expression of glucose transporter genes and inhibiting the binding sites of SGLT1 and GLUT2. Therefore, compounds 1 and 2 may be used as functional foods in dietary therapy for postprandial hyperglycemia modulation of type 2 diabetes.